Examination of interest of things adoption among aquaculturist in Malaysia - Ahmad Khalid, Md. Khairi (2018)
The IoT (internet of things) in Malaysia is still in its infancy stage and the reason to explain the acceptance as well as the understanding of the actual usage level of IoT services remains unclear. Various models have been developed and proposed to increase the understanding of this issue. The proposed model of Unified Theory Acceptance and Use of Technology empirically evaluated by examining the performance expectancy, effort expectancy, social influence, technology complexities, perceived financial cost, facilitating conditions and task technology fit as a moderator in explaining the intention to adopt (IoT) internet of things. Data collected through self-administered survey questionnaire from 282 local aquaculture practitioners in Malaysia. Regression analysis is the main statistical technique applied in this study. The study found that the performance expectancy, effort expectancy, social influence, technology complexities, perceived financial cost and facilitating conditions to have a significant effect on the aquaculture practitioners’ intention to use IoT (internet of things). Task technology fit showed a significant effect as moderator variable on four variables; performance expectancy, effort expectancy, perceived financial cost and facilitating conditions. Overall, the result signifies that the model supports a good understanding of the factors that influence the intention to use towards Internet of Things services. Finally, limitations of the research data were limited to industrial aquaculturists confined to marine and brackish areas. Recommendations for future research is also presented such as to include bigger sampling data on other small aquaculturists.